Storage of Fine Woodchips from a Medium Rotation Coppice Eucalyptus Plantation in Central Italy - Luigi Pari; Simone Bergonzoli; Paola Cetera; Paolo Mattei; Vincenzo Alfano; Negar Rezaei; Alessandro Suardi; Giuseppe Toscano; Antonio Scarfone (Energies, 2020)
Eucalyptus spp. has received attention from the research and industrial field as a biomass crop because of its fast growth and high productivity. The features of this species match with the increasing demand for wood for energy production. Commonly, the wood used for energy production is converted in chips, a material susceptible to microbial degradation and energy losses if not properly stored before conversion. This study aims at investigating two outdoor storage systems of Eucalyptus wood chips (covered vs. uncovered), assessing the variation in moisture content, dry matter losses and fuel characteristics. The class size of the material was P16, which was obtained using a commercial chipper appositely searched to conduct the study. The results highlighted how the different storage methods were influenced by the climatic condition: the woody biomass covered showed the best performances in terms of dry matter losses achieving 2.7% losses vs. the 8.5% of the uncovered systems. However, fuel characteristics displayed minor changes that affected the final energy balance (∆En = −0.2% in covered; ∆En = −6.17% in uncovered). Particle size varied in both methods with respect to the start conditions, but the variation was not enough to determine a class change, which remained P16 even after storage.